Integrating environmental print across the curriculum, preK-3 : making literacy instruction meaningful - Kirkland, Lynn; Aldridge, Jerry; Kuby, Patricia (NU Curriculum., 2007)
This hands-on guidebook highlights the research that supports environmental print (EP) instruction in Grades PreK-3 and provides a wealth of activities for jump-starting the literacy process.